Clinical and morphological analysis of the case of lethal outcome in a patient with Binswanger’s disease - S. V. Vtorushin; O. V. Grebenyuk; V. M. Alifirova; K. Yu. Khristenko; D. V. Vasilchenko; T. A. Valikova; A. A. Ryazantseva (Бюллетень сибирской медицины)
Progressive subcortical vascular leukoencephalopathy caused by chronic hypertension was singled out as a separate disease by Alois Alzheimer and named “Binswanger’s Disease”(BD). Before the introduction of neuroimaging techniques in clinical practice BD was considered as a rare disease and in most cases it was diagnosed during autopsy. More than 80% of BD’s debuts occur on the sixth or seventh decade of life and are characterized by a mild but inexorably progressive course with episodes of exacerbation. At the last stage of the disease, clinical picture is presented by dementia, disorders of the self-service and the pelvic organs functions. The article presents a 42 years-old patient with the terminal stage of the BD’s type vascular dementia verified by postmortem histological examination. It is known that age is an unmodified risk factor for cardiovascular disease. However, in recent decades there has been “vascular risk rejuvenation” of the world, which calls for the development and improvement of approaches to screening and clinical examination of these contingents. The presented case report demonstrates the difficulty in the diagnosis of this pathology of the brain and demonstrates the need for inclusion of the BD in a number of differential diagnostic in patients with cerebrovascular diseases. In addition, we believe that dementia screening should include medical and psychological counseling of patients at risk.